RELIABILITY OF BRAKE SYSTEMS OF BUSES OF GROUP MAZ - A. V. Bessarab (Наука и техника)
All over the world safety of maintained vehicles has the major value. For motor vehicles of the Republic of Belarus this problem is also actual. Maintenance of high reliability of brake systems of cars in operation is one of ways of the decision of a problem of increase of traffic safety.The analysis of reliability of brake systems of buses MAZ is carried out following the results of the state maintenance service in 2010 and the analysis of premature returns from routes of movement of buses MAZ-103 and МАZ-104 one of the motor transportation enterprises of a city of Minsk. Principal causes of structural parameters modification of brake pneumatic system of buses, the brake mechanism and elements АBS are considered.